Images of Korea I [videorecording] - Corps, Sejong Enterprises
The new life style in Seoul are still in harmony in all, there the heritage of ancestors is preserved. Contemporary culture and original art can be seen in the Metropolis. Presents the Hanbok, a traditional customes, folk festivals and games, masked dance drama, traditional Korean wedding ceremony and the old and new buildings.